Role of livestock sector in bridging income inequality among agricultural households in India [An abstract] - Jagadeesh, M. S.; Kuriachen, Philip; Vinay, H. T.; Kumar, S. (Indian Society of Agricultural Economics, 2024)
Income inequality in India poses significant challenges, particularly within agricultural households. This study examines the role of livestock in reducing income inequality among these households by using data from the ‘Situation Assessment Survey of Agricultural Households’ (NSSO 77th round, 2019). The Gini coefficient was used to measures income inequality, and regression-based decomposition analysis to identify the contribution of different income sources to overall inequality. The findings highlight that livestock income plays a crucial role in mitigating income inequality. Crop income constitutes the largest share of total revenue but also shows high inequality, especially in South India. Livestock income, despite regional disparities, emerges as a significant equalizer, particularly in reducing inequality in lower-income households. The study underscores the potential of livestock to enhance rural livelihoods, with states like Chhattisgarh and Kerala exhibiting notable disparities in livestock income distribution. Inequality decomposition reveals that one percent increase in the livestock share in total income can reduce inequality by 1.24 per cent. Moreover, increasing livestock productivity and income can significantly bridge the income gap, fostering equitable growth in rural communities. Policies targeting livestock sector enhancement are essential for reducing poverty, improving resilience, and combating food insecurity. This research highlights the importance of integrating livestock development into broader economic strategies to achieve sustainable and inclusive rural development. The findings contribute to understanding how targeted interventions in the livestock sector can address income inequality among agricultural households in India.